The Rights to Nationality for Ex ISIS Combatants Repatriation Under International Law - Yordan Gunawan; Ravenska Marchdiva Sienda; Rizaldy Anggriawan; Andi Agus Salim (Jurnal Hubungan Internasional, 2022)
In 2020, the Coordinating Minister for Political, Legal, and Security Affairs of Indonesia, Mahfud MD, affirmed that any Indonesian citizen affiliated with ISIS would not be repatriated. However, Article 28D of the 1945 Constitution ensures that a person’s citizenship status is guaranteed as one of the human rights, as guaranteed in Article 15 of the Universal Declaration of Human Rights. For this reason, this research used a normative legal research method using statute and case approaches through literature review. The research raises the question of how is the protection of the rights to nationality for ex-ISIS based on international law? The research aims to discuss and analyze the rights to the nationality of ex-ISIS combatants under the implementation of international law, such as Article 1 (1) of the 1954 Convention Relating to the Status of Stateless Persons. The research results explain that the state’s discretion regarding nationality is particularly limited to conditions such as the prohibition of arbitrary deprivation, the duty to avoid statelessness, and the principle of discrimination, and everyone has a right to a nationality.